1980
DOI: 10.1002/aja.1001570109
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural study of tension and pressure zones in a rabbit flexor tendon

Abstract: The flexor digitorum profundus tendon of the rabbit hind limb is subject to tensional forces throughout most of its length but, within a localised area which is in contact with the calcaneum and talus, it is subjected to additional compressive forces. This pressure-bearing area, in marked contrast to the tensional areas, has a fibrocartilage-like organization and a high concentration of glycosaminoglycans (GAG).Ultrastructural features of the cells, collagen and matrix in the tension and pressure zones are als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
64
1
4

Year Published

1982
1982
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 157 publications
(81 citation statements)
references
References 39 publications
12
64
1
4
Order By: Relevance
“…On the concave (pressure) side the GAG content is -2.3-3.5%, of which 60% is chondroitin sulphate, whilst the associated collagen fibrils have a mass-average diameter of -150nm; in the tensional parts of the tendon, the GAG content is -0.2% (70% being dermatan sulphate) and the fibrils have a mass-average diameter -200 nm [44]. It has also been found that if the tendon is translocated forward so that it is subjected only to tensional forces, profound biochemical and morphological changes occur [35,43,45].…”
Section: Discussionmentioning
confidence: 99%
“…On the concave (pressure) side the GAG content is -2.3-3.5%, of which 60% is chondroitin sulphate, whilst the associated collagen fibrils have a mass-average diameter of -150nm; in the tensional parts of the tendon, the GAG content is -0.2% (70% being dermatan sulphate) and the fibrils have a mass-average diameter -200 nm [44]. It has also been found that if the tendon is translocated forward so that it is subjected only to tensional forces, profound biochemical and morphological changes occur [35,43,45].…”
Section: Discussionmentioning
confidence: 99%
“…18 However, Type II collagen has been shown to be present in both medial meniscal attachments in the uncalcified fibrocartilage, calcified fibrocartilage, and the ligamentous zone 16 ; as well as aggrecan has been found in insertion sites of ligaments. 34 Inasmuch as this type of collagen, usually found where aggrecan is present, 27 is normally related with compression and shear forces, 29,32 we might speculate that both insertion sites in meniscal attachments are subjected to tensile and compressive load in the loaded knee joint. It should be noted that our GAG fraction analysis is only semi-quantitative, comparing only relative amounts of GAG between regions and zones based on staining intensity.…”
Section: Discussionmentioning
confidence: 99%
“…In general, tendon matrices are composed of collagen (mainly type I collagen) GAGs and PGs (19,25). Little alteration from the reaction of azan staining in the incubated tendon tissue blocks was found, suggesting that the amount of collagen fibrils in the tendon changed very little during the incubation period of 96 h. To understand the collagen turnover (synthesis and decomposition of collagen fibrils) in cultured tendon tissue blocks, we are currently carrying out an experiment to determine whether the blocks of tendon tissue have the ability to synthesis collagen fibrils during incubation.…”
Section: Discussionmentioning
confidence: 99%